Just listen : discover the secret to getting through to absolutely anyone - Goulston, Mark; Ferrazszi, Keith (fwd.) (New York Amacom, 2010)
Getting through to someone is a fine art, indeed, but a critical one nonetheless.Whether you are dealing with a harried colleague, a stressed-out client, or an insecure spouse, things will go from bad to worse if you can't break through emotional barricades and get your message thoroughly communicated and registered. Drawing on his experience as a psychiatrist, business consultant, and coach, author mark goulston shares simple but powerful techniques readers can use to break through the stubborn and hardened outer layers of co-workers, friends, strangers, or even enemies. Just listen reveals how to: make a powerful and positive first impression listen effectively talk an angry or aggressive person away from an unproductive reaction and toward a more rational mind-set achieve buy-in$1 (Bthe linchpin of all persuasion, negotiation, and sales and more whether you$1 (Bre dealing with an angry client, a potential customer, or even a friend or family member who isn't seeing eye to eye with you, your goal is most likely persuasion. And the first make-or-break step to getting there is having them hear you out. The invaluable principles in just listen will get you through that first tough step with anyone.s
Keywords: Business communication; Interpersonal communication